Charlotte Streck, IPCC WGIII event, April 16, 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Opportunities and recommendations for mitigating climate change in agriculture: Results from a study commissioned by the Climate and Land Use Alliance -- Charlotte Streck, Climate Focus Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Washington, DC